Semiotic Analysis Of Peace In Salaamun Alaikum By Anis Syusyan According To Michael Riffatere Theory - As'ad, Jinani Firdausi; Sabiila, Diyanah Hanin (Journal of Arabic Language Studies and Teaching, 2024)
The poem "Salamun 'Alaikum" by Anis Chouchene is a compelling subject for analysis due to its exploration of the theme of peace, which was once lost in Tunisia. This study aims to uncover the full significance of the poem. Utilizing Riffaterre's semiotic approach, the research involved text observation, data source identification, and multiple readings of the poem. The findings are summarized as follows: (1) Heuristic reading reveals that the poem employs accessible language and personification, along with numerous affirmations to underscore the poet's viewpoint. (2) Hermeneutic reading suggests that the poem is a response to an incident of racism in Tunisia, with the poet expressing personal feelings and recommending actions for Tunisian citizens. (3) The underlying matrix of the poem is the theme of peace, which the poet seeks to communicate to the broader public, especially the Tunisian population, which was grappling with racism at the time.